Oblivious hashing: A stealthy software integrity verification primitive - Chen, Yuqun; Venkatesan, Ramarathnam; Cary, Matthew; Pang, Ruoming; Sinha, Saurabh; Jakubowski, Mariusz (Information Hiding 2002, 2002)
We describe a novel software verification primitive called Oblivious Hashing. Unlike previous techniques that mainly verify the static shape of code, this primitive allows implicit computation of a hash value based on the actual execution (i.e., space-time history of computation) of the code. We also discuss its applications in local software tamper resistance and remote code authentication.